CONCEPTUAL METAPHORS AND CULTURAL MODELS IN ENGLISH, UZBEK, AND RUSSIAN PROVERBS (International journal of artificial intelligence, 2025)
Proverbs are among the most culturally saturated elements of any language. They encapsulate centuries of collective experience and serve as compact cultural codes transmitting values, emotions, and wisdom. When viewed from the lens of cognitive linguistics, proverbs reveal underlying conceptual metaphors — mental mappings that connect the concrete and the abstract, shaping how speakers of different languages perceive and interpret the world. From a linguocultural perspective, these metaphors do not exist in a vacuum; they are embedded in national traditions, religious thought, social behavior, and the linguistic structure of each culture (Kövecses, 2002). Examining English, Uzbek, and Russian proverbs through this dual cognitive and cultural framework allows for a deep understanding of how language, thought, and culture intertwine.